Analisis User Experience Pada Aplikasi Mobile Alfagift dengan Menggunakan Metode Heart Metrics - Mulyadi, Mulyadi; Meiriza, Allsela; Oktadini, Nabila Rizky; Putra, Pacu; Sevtiyuni, Putri Eka (Journal of Information System Research (JOSH), 2024)
Alfagift is a mobile-based application launched in 2015 by alfamart. Alfagift mobile application has 6 interesting features in the form of making it easier for users to get various benefits provided by the Alfagift application. The six features in question include Offer (Promo), Voucher, Catalogue, Messages, Store Locator, and Contact Us. As a loyal alfamart customer, you must have this application to get the benefits that have been provided. Plus, using the Alfagift application will get various other benefits. There are problems such as frequent failed transactions, no information about expiration dates , applications often experience technical problems such as bugs and not all people can use it because the interface is too complex. The purpose of the study is to analyse the user experience of Alfagift users in the form of 5 variables in Heart Metrics and suggest improvements for the Alfagift application in the future so that it becomes a better application. This study used 100 people in Palembang city, based on the answers from respondents, the results of 5 different variables were obtained in the form of Happiness getting a percentage of 73.13%, Engagement getting a percentage of 77.2%, Adoption getting a percentage of 76.8%, Retention getting a percentage of 72.93%, Task success getting a percentage of 76.26%, and overall getting a percentage of 75.26% so that it can be stated that the alfagift application is classified as good.